2022
DOI: 10.1186/s12889-022-12886-7
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated workers: overlooked as essential workers

Abstract: Objective To use the example of COVID-19 vaccine prioritization for incarcerated workers to call attention to the need to prioritize incarcerated workers’ health. Methods From November to December 2020, we searched publicly available information (e.g. Department Of Corrections websites and press releases) for 53 US prison systems, including all states, Immigration and Customs Enforcement, the Federal Bureau of Prisons, and Puerto Rico. Coders revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Incarcerated people worldwide were given low priority for vaccination, with only 43% of countries with vaccination plans prioritizing incarcerated people 16. In the US, labor policies did not consider incarcerated workers to be essential workers for vaccination (eg, those serving as firefighters) 17. Additionally, over 60% of prison systems worldwide experienced overcrowding, and while some released substantial numbers of people early in the pandemic, many systems have begun returning to pre-pandemic levels (eg, England and Wales) 18…”
Section: Covid-19 In American Prisons and Jailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incarcerated people worldwide were given low priority for vaccination, with only 43% of countries with vaccination plans prioritizing incarcerated people 16. In the US, labor policies did not consider incarcerated workers to be essential workers for vaccination (eg, those serving as firefighters) 17. Additionally, over 60% of prison systems worldwide experienced overcrowding, and while some released substantial numbers of people early in the pandemic, many systems have begun returning to pre-pandemic levels (eg, England and Wales) 18…”
Section: Covid-19 In American Prisons and Jailsmentioning
confidence: 99%
“…Covid-19 showed that the prison and jail infrastructure is not adequately prepared to protect health in the next public health crisis, the climate crisis. As noted above, prisons and jails are overcrowded,36 have poor ventilation,37 and have inadequate labor policies for incarcerated workers 17. Furthermore, few academic publications, administrative data, or policy documents are available to help predict and ameliorate the effect of factors such as extreme temperatures in carceral settings or an increase in climate disasters that may affect the health of prisoners and the prison environment 38…”
Section: Future Crisis Preparationmentioning
confidence: 99%